3-Dimensional analysis of fatigue crack fields and crack growth by in situ synchrotron X-ray tomography. (May 2023) - Koko, A.; Singh, S.; Barhli, S.; Connolley, T.; Vo, N.T.; Wigger, T.; Liu, D.; Fu, Y.; Réthoré, J.; Lechambre, J.; Buffiere, J.-Y.; Marrow, T.J.
Highlights: In situ three-dimensional observation of curved fatigue crack propagation. Measurement of the three-dimensional crack shape and crack tip displacement field. The local mode I stress intensity factor range of the open crack determines the crack growth rate. Abstract: The propagation rate of a fatigue crack in a nodular cast iron, loaded in cyclic tension, has been studied in situ by X-ray computed tomography and digital volume correlation. The semi-elliptical crack initiated from an asymmetric corner notch and evolved to a semi-circular shape, initially with a higher growth rate towards one edge of the notch before the propagation rate along the crack front became essentially independent of position. The phase congruency of the displacement field was used to measure the crack shape. The three-dimensional stress intensity factors were calculated via a linear elastic finite element model that used the displacement fields around the crack front as the boundary conditions. Closure of the crack tip region was observed. The cyclic change in the local mode I opening of the crack tip determined the local fatigue crack propagation rate along the crack front.